When Exchange Fails: A Maqāṣid-Based Socio-Legal Inquiry into Reciprocity and Rationality in Islamic Divorce - Ishaq; Gorski Noor Bellah; Helena Rocha Vauclair; Moh. Wasik; Abdifatah Ouich Mustache (Indonesian Journal of Islamic Law, 2025)
This study re-examines the phenomenon of divorce through the intersection of social theory and Islamic legal reasoning. It investigates why husband-initiated divorces continue to rise despite the moral discouragement of ṭalāq in Islamic ethics. Integrating George C. Homans’ social exchange theory, Max Weber’s theory of social action, and the maqāṣid al-sharī‘ah framework, the research formulates a tri-theoretical inquiry into reciprocity, rationality, and moral responsibility in marital relationships. Employing a qualitative field approach at the Legal Aid Post (Posbakum) of the Jember Religious Court, data were collected through interviews, observation, and document analysis and examined using the Miles–Huberman interactive model. The findings reveal that divorce decisions are frequently triggered by an absence of appreciation and emotional reciprocity within the household—wives’ failure to express gratitude, provide motivation, or offer constructive support during economic hardship. In Homans’ framework, such an absence reflects the breakdown of success, stimulus, and value propositions. Within the logic of Weberian zweckrational action, divorce emerges as a deliberate, instrumentally rational decision. From the maqāṣid al-sharī‘ah perspective, appreciation and mutual support constitute ḍarūriyyāt essential to marital harmony, while ṭalāq remains a legitimate prerogative of the husband (qawwām) only when exercised with ethical and legal responsibility.